A comparative study on fish biodiversity with conservation measures of the Bhairabriver, Jessore, Bangladesh - Islam, Md Ashraful; Asif, Abdulla Al; Samad, Md Abdus; Sarker, Baadruzzoha; Ahmed, Meraz; Satter, Abdus; Hossain, Amir (Asian Journal of Medical and Biological Research, 2017)
The present study was concerned to assess the present status of biodiversity in the Bhairab river, Jessore with its conservation measures. The study was based on primary observations, questionnaire interviews with 50 fishers, focus group discussions with river bank community members and cross-check interviews with key informants. The study was conducted for a period four months from May to August, 2016. The objective of the study was to assess the fish biodiversity in the Bhairab river, understand the existing fishing practices of the river and to identify proper management strategies for the conservation of fish biodiversity. Results of the study revealed that three kinds of fishers were engaged in the Bhairab river namely, professional fishers; seasonal fishers and subsistence fishers. Seven types of fishing gears like seine net, gill net, cast net, push net, lift net, trap and hook and line were operated to fish by the fishers during the survey. A total of 39 species of fish were identified in the catches of the Bhairab River. There are degraded ecosystems and declining biodiversity have found during the study. According to survey, fishing pressure and over fishing were responsible for almost 38% loss and pollution and siltation caused about 27% loss of ecosystem. Around 21% and 14% loss of ecosystem were caused by urbanization and human encroachment, and the recreational activities respectively. These have been created a great impact on river ecology. As a result, the water quality is deteriorating day by day and the availability of fish species and other aquatic biodiversity is decreasing gradually. During the survey, 20 species was found at a risk of being endangered. From the survey, it was found that the overexploitation of fish was responsible for the 40% losses of biodiversity in the Bhairab River and water pollution caused 35% loss of biodiversity. Henceforth, river course change and habitat degradation resulted in 15% and 10% loss of biodiversity of the river respectively. This study was identified possible ways to achieve a rich fish biodiversity in the Bhairab River with social, economic and environmental aspects. The specific recommendations are included community based fisheries management, establishment of sanctuary, control of pollution, maintenance of fishing gears and the implementation of fish act for conservation of fish biodiversity of the Bhairab River. Asian J. Med. Biol. Res. September 2017, 3(3): 357-367